2022
DOI: 10.1111/codi.16078
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines, guidelines and more guidelines for haemorrhoid treatment: A review to sort the wheat from the chaff

Abstract: Aim Guidelines benefit patients and clinicians by distilling evidence into easy‐to‐read recommendations. The literature around the management of haemorrhoids is immense and guidelines are invaluable to improve treatment integrity and patient outcomes. We identified current haemorrhoid guidelines and assessed them for quality and consistency. Methods A systematic search of the literature from January 2011 to October 2021 was carried out. Guidelines identified were assessed for quality using the AGREE II instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We were not the only ones to rate the ASCRS guideline lower than the authors did: Brown et al ( 3 ) also rated the ASCRS guideline lower. The Italian (SICCR) guideline, that was rated quite high by Graviilidis et al was rated low by Brown et al So, we wonder how the authors come to their rating, that is quite different from Brown et al and ours.…”
mentioning
confidence: 80%
“…We were not the only ones to rate the ASCRS guideline lower than the authors did: Brown et al ( 3 ) also rated the ASCRS guideline lower. The Italian (SICCR) guideline, that was rated quite high by Graviilidis et al was rated low by Brown et al So, we wonder how the authors come to their rating, that is quite different from Brown et al and ours.…”
mentioning
confidence: 80%
“…The "anal cushion weakening" theory emphasizes changes in anatomical structure, whereas the "varicose vein weakening" theory emphasizes changes in blood ow. Numerous studies have shown that the pathogenesis of hemorrhoids is the weakening of the lower anal cushion under the in uence of various factors [7,9,10]: the pressure of the three terminal branches of the in ow of the superior rectal artery increases, and the out ow of the superior, middle, and inferior rectal veins decreases, leading to the dilation of the vascular plexus of the anal-cushion arterial-venular anastomosis, eventually resulting in the formation of hemorrhoids. Based on these theories, effective reduction of anal cushion weakening and protection of the integrity of the anal cushion structure and function are of great importance in the treatment of hemorrhoids [11].…”
Section: Discussionmentioning
confidence: 99%